dBase IV made easy - Liskin, Miriam (New York : McGraw Hill Education, 1989)
This book will help you surmount those barriers and begin doing productive work with dBase IV almost immediately.
1. Introduction to data base management -- 2. Starting and running dbase IV -- 3. Planning and designing a data base -- 4. Entering and updating the data -- 5. Working at the dot prompt -- 6. Selecting fields -- 7. Selecting records -- 8. Sorting a data base -- 9. Indexing a data base -- 10. Performing calculations -- 11. Defining and printing labels -- 12. Printing columnar reports -- 13. Customizing label and report forms -- 14. Printing form and mailmerge reports -- 15. Creating custom data entry forms -- 16. Reorganizing data bases -- 17. Working with multiple data bases.
Includes index.
Keywords: DBASE (COMPUTER PROGRAM LANGUAGE)